2010
DOI: 10.1016/j.jfoodeng.2010.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a chitosan-based edible film as carrier of natamycin to improve the storability of Saloio cheese

Abstract: a b s t r a c tThe purpose of this study was to evaluate the effects of the application of chitosan coating containing natamycin on the physicochemical and microbial properties of semi-hard cheese. Three cheese groups were prepared: samples without coating, samples coated with chitosan and with chitosan containing 0.50 mg mL À1 of natamycin, whose minimum inhibitory concentration was previously determinated on cheese surface. Microbiological analyses showed that natamycin coated samples presented a decrease on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
145
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(171 citation statements)
references
References 33 publications
5
145
1
3
Order By: Relevance
“…Fajardo et al [59] appointed that the absence of differences between Saloio cheeses coated with an edible film containing pimaricin are not to be expected when the counts are performed in the whole cheese samples and not only at their surface and as in this work the results are obtained under no inoculation conditions. In the bioassay with Therefore, despite the antimicrobial effect is not maintained for a long time, as initial microbial load is very high (169x10 7 UFC mL -1 ), the differences founded with respect to the pimaricin treatment evidence the protective effect of the pimaricin-loaded nanohydrogel system observed in the food model system (Section 4.2.1 on page 95) that will allow maintain an antimicrobial effect of pimaricin for longer.…”
Section: Antimicrobial Effectiveness Of Pimaricin-loaded Nanohydrogelmentioning
confidence: 66%
See 1 more Smart Citation
“…Fajardo et al [59] appointed that the absence of differences between Saloio cheeses coated with an edible film containing pimaricin are not to be expected when the counts are performed in the whole cheese samples and not only at their surface and as in this work the results are obtained under no inoculation conditions. In the bioassay with Therefore, despite the antimicrobial effect is not maintained for a long time, as initial microbial load is very high (169x10 7 UFC mL -1 ), the differences founded with respect to the pimaricin treatment evidence the protective effect of the pimaricin-loaded nanohydrogel system observed in the food model system (Section 4.2.1 on page 95) that will allow maintain an antimicrobial effect of pimaricin for longer.…”
Section: Antimicrobial Effectiveness Of Pimaricin-loaded Nanohydrogelmentioning
confidence: 66%
“…For example, chitosan-based edible films [59], wheat gluten and methyl cellulose biopolymers [192,191] and polyethylene films coated with commercially available polyvinylchloride (PVC) lacquer coatings [81], whey protein films [148], alginate-based coatings [134], cellulosebased films [136].…”
Section: Figure 1 Pimaricin Moleculementioning
confidence: 99%
“…By appliying coatings/films on cheese surfaces moisture condensation/migration can be controlled. The exchange of natural vapourable flavor compounds and color compounds between the cheese and its surrounding environment can be restricted as the coating acts as gas barrier (Mei et al 2000;Cerqueira et al 2009;Fajardo et al 2010;Pierro et al 2011). Lipid compounds exploited as edible polymers consist of acetylated monoglycerides, paraffin wax, beeswax and surfactants.…”
Section: Edible Films and Coatings In Cheesementioning
confidence: 99%
“…Ojagh et al [37] extended the shelf-life of Rainbow trout (a fish native of North America) during 16 days at 4ºC incorporating cinnamon oil (at 1.5%) into a matrix of chitosan-based edible coating. Fajardo et al [38] evaluated the antifungal activity of chitosan-based edible coating containing 0.5mg/mL natamycin on semi-hard "Saloio" cheese; and demonstrated that populations of moulds and yeasts were reduced by about 1.1 log CFU/g compared to control samples after 27 days of refrigerated storage. Jiang et al [29] showed that a combination of sodium lactate and sodium diacetate incorporated into chitosan edible coating was able to inactivate L. monocytogenes on ready-to-eat roasted turkey stored at 4°C.…”
Section: Carriers Of Antimicrobial Compoundsmentioning
confidence: 99%